Ano-recto-cutaneous fistulas - Gómez Fossati, Carlos; Estefan Segui, Alberto (Cirugía del Uruguay, 1973)
Gabriel (35), defines fistulas as an "abnormal communication between 2 cavities or between a cavity and the external surface".